The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acssynbio.0c00330
|View full text |Cite
|
Sign up to set email alerts
|

Transcription and Translation in Cytomimetic Protocells Perform Most Efficiently at Distinct Macromolecular Crowding Conditions

Abstract: The formation of cytomimetic protocells that capture the physicochemical aspects of living cells is an important goal in bottom-up synthetic biology. Here, we recreated the crowded cytoplasm in liposome-based protocells and studied the kinetics of cell-free gene expression in these crowded containers. We found that diffusion of key components is affected not only by macromolecular crowding but also by enzymatic activity in the protocell. Surprisingly, size-dependent diffusion in crowded conditions yielded two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 73 publications
1
40
0
Order By: Relevance
“…The first possibility we tested was that inadequate small molecule environments such as magnesium concentration reduced CFPS activity. A previous study showed a high concentration of magnesium can restore the decrease of CFPS activity using HCCE [ 34 ]. To test the possibility, CFPS activity of HCCE under various magnesium concentrations was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…The first possibility we tested was that inadequate small molecule environments such as magnesium concentration reduced CFPS activity. A previous study showed a high concentration of magnesium can restore the decrease of CFPS activity using HCCE [ 34 ]. To test the possibility, CFPS activity of HCCE under various magnesium concentrations was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…This observation is consistent with a previous study showing that crowding had distinct effects on isoenzymes of β-galactosidase with different rate-limiting steps [ 99 ]. Furthermore, there is precedent gene regulation studies that crowding can alter the rate-limiting step of a reaction [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…For transition-state-limited reactions, though, crowding effects are less predictable due to the complex, often opposing, interplay of excluded volume, viscosity, soft interactions, and hydration effects [ 9 ]. These trends are further complicated by the fact that crowding has differing effects on steps within an enzymatic process and can thereby alter the rate-limiting step of a reaction [ 10 ]. Excluded volume can increase enzyme activity by improving substrate binding [ 11 ], stabilizing the enzyme [ 12 ], or promoting the proper oligomerization state [ 13 ]; yet, crowding can also decrease enzyme activity by enhancing product inhibition [ 14 ], altering thermodynamic activities [ 15 ], impeding a critical conformational change [ 16 ], aggregating the enzyme [ 17 ], interacting with the substrate [ 18 ], or dehydrating the protein [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the classical MC effects are supposed to be largely independent of the nature of "crowder" (which is not always observed in reality), and the typical in vitro crowding experiment often uses inert polymers (dextran, Ficoll, or polyethylene glycol) to mimic the environment inside the cell [9]. The next approximation to nature can be achieved by encapsulating the reagents and crowders in liposomes [10][11][12]. In this paper, we will look at the crowding effects from the CV regulation perspective, including their possible roles in the regulatory volume responses, volume sensing, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%